2019
DOI: 10.1007/s40195-019-00963-7
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion and Cavitation Erosion Behaviours of Cast Nickel Aluminium Bronze in 3.5% NaCl Solution with Different Sulphide Concentrations

Abstract: The effect of sulphide (Na 2 S) concentration (SC) on the corrosion and cavitation erosion behaviours of a cast nickel aluminium bronze (NAB) in 3.5% NaCl solution is investigated in this study. The results show that when the SC exceeds 50 ppm, the hydrogen evolution reaction dominates the cathodic process, and a limiting current region appears in the anodic branch of the polarisation curve due to the formation of a copper sulphide film, which is a diffusion-controlled process. After longterm immersion, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
(75 reference statements)
0
19
0
Order By: Relevance
“…Furthermore, increasing sulphide concentration in the range of 20 to 100 ppm led to deterioration of corrosion properties. 114 Cu + HS − → Cu(HS) ads + e − Cu + Cu(HS) ads + HS − → Cu 2 S + H 2 S + e − These findings emphasized the profound effect of solution type on the corrosion behavior of NAB. 86,113,114 A recent comparative study, conducted in simulated seawater (SSW) and simulated freshwater (SFW) revealed that NAB alloy experienced localized attack in SFW due to the presence of sulphate and bicarbonate in the environment, which hindered the attainment of equilibrium.…”
Section: Corrosion Behavior Of Conventional Nab Alloysmentioning
confidence: 78%
See 4 more Smart Citations
“…Furthermore, increasing sulphide concentration in the range of 20 to 100 ppm led to deterioration of corrosion properties. 114 Cu + HS − → Cu(HS) ads + e − Cu + Cu(HS) ads + HS − → Cu 2 S + H 2 S + e − These findings emphasized the profound effect of solution type on the corrosion behavior of NAB. 86,113,114 A recent comparative study, conducted in simulated seawater (SSW) and simulated freshwater (SFW) revealed that NAB alloy experienced localized attack in SFW due to the presence of sulphate and bicarbonate in the environment, which hindered the attainment of equilibrium.…”
Section: Corrosion Behavior Of Conventional Nab Alloysmentioning
confidence: 78%
“…114 Cu + HS − → Cu(HS) ads + e − Cu + Cu(HS) ads + HS − → Cu 2 S + H 2 S + e − These findings emphasized the profound effect of solution type on the corrosion behavior of NAB. 86,113,114 A recent comparative study, conducted in simulated seawater (SSW) and simulated freshwater (SFW) revealed that NAB alloy experienced localized attack in SFW due to the presence of sulphate and bicarbonate in the environment, which hindered the attainment of equilibrium. 87 On the other hand, when exposed to SSW, it rapidly formed a relatively protective film on the surface.…”
Section: Corrosion Behavior Of Conventional Nab Alloysmentioning
confidence: 78%
See 3 more Smart Citations